(untitled) (Research, Society and Development, 2025)
Generalized Anxiety Disorder (GAD) is a highly prevalent psychiatric condition, characterized by persistent worry and diffuse somatic symptoms, with significant impact on functionality, quality of life, and the healthcare system. Objective: To critically review the current literature on pharmacological interventions for GAD, focusing on efficacy, safety, clinical applicability, and therapeutic gaps. Materials and Methods: An exploratory integrative review was conducted across four databases (BVS, SciELO, Google Scholar, and PubMed), using the PICO approach and systematic selection criteria, with 20 articles fully analyzed between 2010 and 2025. Results and Discussion: Although SSRIs and SNRIs remain first-line therapies, clinical limitations such as partial response and sustained adverse effects justify the growing use of alternatives like pregabalin, quetiapine, and multimodal antidepressants (vilazodone, vortioxetine), as well as emerging approaches with ketamine, agomelatine, and glutamatergic or chronobiological agents. These interventions show benefits in specific subgroups but still face methodological, economic, and safety constraints that limit widespread implementation. Conclusion: Despite the expansion of the pharmacological arsenal, major challenges remain in the individualized management of GAD, especially given clinical heterogeneity and the lack of predictive biomarkers. The consolidation of personalized medicine strategies, supported by pragmatic studies and equitable access policies, will be essential to improve the real-world effectiveness of pharmacological interventions.